Role of Carotenoids in Ornamental Fish Nutrition: A Review - Pailan, G. H.; Sahoo, Sujata; Singh, D. K. (Indian Journal of Animal Nutrition, 2019)
A bright colourful fish is the primary attraction of an aquarium. This colouration is due to skin pigments, underlying tissues and body fluids. Carotenoids are the major group of colouring pigments among similar other compounds. They also have a significant role in the reproduction, respiration, membrane permeability, light absorption, reflection and the efficiency of the immune system etc. Unfortunately, fish, cannot produce the carotenoids themselves and are reliant upon a dietary source. Coloured fish often show faded or degraded coloration especially when the fishes are kept under captivity and also in intensive culture condition. This faded colouration can be improved with feed containing either pure natural /synthetic carotenoids directly or indirectly through natural sources of microbial, plant and animal origin. This review article deals with carotenoids, their types, function, sources and physiological effect on fish in a comprehensive manner.